2019
DOI: 10.1002/cne.24684
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and subcellular localization of Copines in mouse retina

Abstract: Combinatorial expression of Brn3 transcription factors is required for the development of cell‐specific morphologies in retinal ganglion cells (RGCs). The molecular mechanisms by which Brn3s regulate RGC type specific features are largely unexplored. We previously identified several members of the Copine (Cpne) family of molecules as potential targets of Brn3 transcription factors in the retina. We now use in situ hybridization and immunohistochemistry to characterize Copine expression in the postnatal and adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 49 publications
4
16
1
Order By: Relevance
“…Muscles were kept in PBS at 4 °C until mounted in Vectashied (Vector labs). Primary antibodies used in immunohistochemistry experiments were: Rb anti-Calbindin D-28k (1:2,000) (Swant), Rb anti-Calretinin (Calb2; 1:2000) (Swant), Gp anti-tdTomato (1:32,000) 28 , Rb anti-dsRED (1:1000) (Clontech), Rb anti-GFP (1:1000) (ThermoFisher), Shp anti-GFP (1:500) (AbD Serotec), Rt anti-Troma1 (1:100) (DSHB), Rt anti-Substance P (1:200) (Santa Cruz Biotechnology), Rb anti-Rx3 (1:50,000) 65 , Gp anti-Rx3 (1:16,000) 66 , Ck anti-PV (1:30,000) 27 , Gp anti-Islet 1 (1:20,000) 67 , Rb anti-vGlut1 (1:16,000) 68 , Rb anti-VGlut2 (1:500) (Synaptic Systems), Rb S-100 (1:400) (Agilent), Ck anti-Brn3c (Pou4f3) (1:50) 69 , Ck anti-b-galactosidase (1:5,000) (Abcam), Rb anti-PCDH8 (1:250) (Millipore). Fluorophore-conjugated secondary antibodies generated in donkey (Jackson Immuno Research Laboratories) were used at 1:1000 (FITC) or 1:500 (Cy3, Cy5) in PBS, 1% BSA, 0.1% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
“…Muscles were kept in PBS at 4 °C until mounted in Vectashied (Vector labs). Primary antibodies used in immunohistochemistry experiments were: Rb anti-Calbindin D-28k (1:2,000) (Swant), Rb anti-Calretinin (Calb2; 1:2000) (Swant), Gp anti-tdTomato (1:32,000) 28 , Rb anti-dsRED (1:1000) (Clontech), Rb anti-GFP (1:1000) (ThermoFisher), Shp anti-GFP (1:500) (AbD Serotec), Rt anti-Troma1 (1:100) (DSHB), Rt anti-Substance P (1:200) (Santa Cruz Biotechnology), Rb anti-Rx3 (1:50,000) 65 , Gp anti-Rx3 (1:16,000) 66 , Ck anti-PV (1:30,000) 27 , Gp anti-Islet 1 (1:20,000) 67 , Rb anti-vGlut1 (1:16,000) 68 , Rb anti-VGlut2 (1:500) (Synaptic Systems), Rb S-100 (1:400) (Agilent), Ck anti-Brn3c (Pou4f3) (1:50) 69 , Ck anti-b-galactosidase (1:5,000) (Abcam), Rb anti-PCDH8 (1:250) (Millipore). Fluorophore-conjugated secondary antibodies generated in donkey (Jackson Immuno Research Laboratories) were used at 1:1000 (FITC) or 1:500 (Cy3, Cy5) in PBS, 1% BSA, 0.1% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
“…To date, there are nine copines (1–9) identified in mammals, ubiquitously expressed in diverse tissues such as heart, lungs, spleen, kidneys, prostate and brain [ 305 , 307 , 308 , 309 , 310 , 311 , 312 , 313 ]. Although the precise function of copines in mammalian cells remains unclear, evidence suggests that they are involved in regulating signaling pathways [ 306 ], in membrane trafficking [ 314 ] and in morphogenetic processes associated with the maturation of retinal synaptic architecture [ 315 ].…”
Section: Copinesmentioning
confidence: 99%
“…GST tagged Cpne4 protein was synthesized from bacteria as described before (23). GST-Cpne4-vWAdomain and GST proteins were also synthesized similarly.…”
Section: Methodsmentioning
confidence: 99%
“…In the retina, we have previously reported that Cpne4, 5, 6 and 9 are enriched in the inner retina and they are regulated by Brn3b and Brn3a (1,23). Whereas Cpne5, 6 and 9 were expressed in most of the GCL as well as INL, Cpne4 is the only Copine specifically expressed in RGCs (with the exception of one INL amacrine cell type) (23).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation